Resultado da implantação de um Núcleo Interno de Regulação de Leitos nos indicadores administrativo-assistenciais em um hospital de ensino - Rodrigues, Luciane Cristine Ribeiro; Juliani, Carmen Maria Casquel Monti [UNESP] (FapUNIFESP (SciELO), 2015)
Objective To compare hospital indicators before and after implementing an Internal Bed Regulation Committee at a reference hospital. Methods It is an quantitative, evaluation, exploratory, descriptive and cross-sectional research. The data was gathered from the hospital administrative reports for the period 2008-2013, provided by the Information Technology Center of the Complexo FAMEMA. Results The indicators improved after implementation of the Internal Bed Regulation Committee. Conclusion The individuals involved in the process acknowledged the improvement. It is necessary to carry on the regulatory actions, especially in a comprehensive and complex healthcare system, such as the brazilian Sistema Único de Saúde.

Objetivo: Comparar indicadores hospitalares antes e após a implantação de um Núcleo Interno de Regulação de Leitos em um hospital de referência. Métodos: Pesquisa avaliativa, exploratória, descritiva e transversal, de natureza quantitativa. Os dados apresentados foram extraídos de relatórios administrativos do hospital, fornecidos pelo Núcleo Técnico de Informática do Complexo FAMEMA, abrangendo o período de 2008 a 2013. Resultados: Os indicadores apresentaramse melhores após a implantação do Núcleo Interno de Regulação. Conclusão: As melhorias foram sentidas pelos sujeitos envolvidos no processo. Há necessidade de continuidade das ações regulatórias, em especial em um sistema de saúde abrangente e complexo, como é o Sistema Único de Saúde na realidade brasileira.
Impact of implementing an Internal Bed Regulation Committee on administrative and care indicators at a teaching hospital
Keywords: Hospital administration; Bed occupancy; Health services accessibility; Health care regulation and supervision; Health status indicators; Administração hospitalar; Ocupação de leitos; Acesso aos serviços de saúde; Regulação e fiscalização em saúde; Indicadores básicos de saúde